Clinical profile of carcinoma breast cases at a tertiary care hospital - Almas, Arifa (International Surgery Journal, 2017)
Background: Breast carcinoma is a serious health problem and is among the major health issues in India. Also, it has a relatively early age presentation in this part of the world. Present study describes the features like age at presentation, clinical stage at presentation and incidence of regional lymph node involvement and distant metastases among the breast cancer patients at Government Medical College, Jabalpur in Madhya Pradesh, India. Methods: This hospital-based descriptive study was conducted at the Department of Surgery, Government Medical College, Jabalpur in Madhya Pradesh state of India. Fifty patients with a confirmed diagnosis of breast cancer were included in the study. The details like age at presentation, clinical stage at presentation and incidence of regional lymph node involvement and distant metastases among the breast cancer patients were described and tabulated. Results: Youngest patient of the series was aged 30 years whereas the oldest was aged 65 years. Maximum patients belonged to 41 to 50 years age group. Stage wise distribution of cases reflected that Stage III was the most common stage at presentation. Majority of the cases had lymph node involvement (90%). Liver metastasis was seen in 8 cases (16%), of which, 2 cases had ascites. There were 6 cases of lung metastasis, of which 2 cases had pleural effusion and remaining 4 cases showed solitary metastasis. 6 cases of osseous metastasis were observed, out of which, 2 cases had skull metastasis and 4 cases had spine involvement. Conclusions: It was found that the age group in majority of the patients was younger as compared to Western world and this finding is in line with data from India and other Asian regions. Also, there was a presentation at a later stage of disease in our study population.